Crosstalk of Oncogenic Signaling Pathways during Epithelial–Mesenchymal Transition - Lindsey, Stephan; Langhans, Sigrid A. (Frontiers in Oncology, 2014)
Epithelial-mesenchymal transition (EMT) and cell transformation have been well-documented in multiple cancer cell models and are believed to be one of the earliest events in tumor progression. Genetic and epigenetic modifications shift cells toward either end of the EMT spectrum, and can be influenced by the microenvironment surrounding a tumor. EMT and mesenchymal-epithelial transition (MET) are critical to normal function and development and an intricate network of transcription factors and transcriptional regulators tightly regulates these processes. As evidenced in normal and transformed cell lines, many signaling pathways trigger EMT during development and differentiation. The signaling pathways include those triggered by different members of the transforming growth factor (TGF) superfamily, epidermal growth factor (EGF), fibroblast growth factor (FGF), hepatocyte growth factor (HGF), hypoxia-inducible factor (HIF), Wnt, Notch, and many others. Functional redundancies allow cells to undergo EMT even if these key transcriptional regulators are lacking, but these same redundancies also make these pathways particularly susceptible to gain-of-function mutations or constitutive signal activation; the “forced” transition toward either a mesenchymal or epithelial phenotype.